2022
DOI: 10.22270/jddt.v12i6.5787
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Various Manufacturing Approaches for Developing Amorphous Solid Dispersions

Abstract: In recent years amorphous solid dispersions (ASD) has gained a tremendous response for improving the solubility of poorly water-soluble drug substances. Despite the stability challenges, various ASD commercial products have been successfully launched into the market over the last two decades. Among various manufacturing approaches, hot melt extrusion (HME) and spray drying techniques have attracted industries attributing to their simple manufacturing processes. In addition, KinetisolÒ, a solvent-free approach,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 84 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…Particularly, natural source components, such as cellulose, chitosan, lignin, and polysaccharide, are the favorite polymeric carriers ( Huang, et al, 2022a ; Chen, et al, 2022c ; Wang, et al, 2022 ; Liu, et al, 2023b ). Pharmaceutical techniques are often a key element for ensuring acceptable SD compatibility between the drug and excipients, a favorable amorphous state (i.e., amorphous solid dispersions, ASDs), and reasonable morphology and structures for simple dosage transformations ( Konda & Dhoppalapudi, 2022 ; Tan, et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, natural source components, such as cellulose, chitosan, lignin, and polysaccharide, are the favorite polymeric carriers ( Huang, et al, 2022a ; Chen, et al, 2022c ; Wang, et al, 2022 ; Liu, et al, 2023b ). Pharmaceutical techniques are often a key element for ensuring acceptable SD compatibility between the drug and excipients, a favorable amorphous state (i.e., amorphous solid dispersions, ASDs), and reasonable morphology and structures for simple dosage transformations ( Konda & Dhoppalapudi, 2022 ; Tan, et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo studies have shown that these factors are critical for determining the success of oral formulations, so understanding their intricate workings is fundamental to improving results. Through careful analysis in vitro, researchers can gain insight into how they might be able to improve those rates and thus ultimately enhance the efficacy of such treatments [4][5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%